Writing the author: Sylvia Plath, Henry James, Virginia Woolf and the biographical novel - Hudson, Elaine C. (2015)
This thesis explores the effect produced when contemporary novelists write about fellow authors. Since the mid-1990s, the biographical novel, which fictionalises the lives of real-life historical authors, has become an increasingly popular literary genre in Britain and the United States. This contemporary exploration of authorial subjectivity, viewed here through the lens of life-writing, provides a reengagement with debates surrounding the crisis of the author-figure (exemplified by Roland Barthes), and the unreliability of biography as a discourse of subjectivity at the turn of the twenty-first century. Through its inherent self-reflexivity (with its exposure of both the author-biographer alongside the author-subject), I consider how the biographical novel succeeds in reconciling the author-figure with the literary text in new ways.